Image‐guided IMRT with simultaneous integrated boost as per RTOG 0529 for the treatment of anal cancer. Issue 3 (30th August 2017) - Arcadipane, Francesca; Franco, Pierfrancesco; Ceccarelli, Manuela; Furfaro, Gabriella; Rondi, Nadia; Trino, Elisabetta; Martini, Stefania; Iorio, Giuseppe Carlo; Mistrangelo, Massimiliano; Cassoni, Paola; Racca, Patrizia; Morino, Mario; et al.
Abstract: Aim: To report on clinical outcomes of simultaneous integrated boost intensity‐modulated radiation therapy (IMRT) and concurrent chemotherapy as per Radiation Therapy Oncology Group (RTOG) 0529 protocol in anal cancer patients. Methods: Clinical stage T1–T4 N0–N3 anal cancer patients were submitted to concomitant chemoradiation. Patients with cT2N0 disease were prescribed 50.4 Gy/28 fractions to the gross tumor planning target volume (PTV) and 42 Gy/28 fractions to the elective nodal PTV. Patients staged as cT3–T4/N0–N3 were given 54 Gy/30 fractions to the macroscopic anal PTV, while clinical nodes were prescribed 50.4 Gy/30 fractions if <3 cm or 54 Gy/30 fractions if ≥3 cm; elective nodal PTV was prescribed 45 Gy/30 fractions. Two cycles of concomitant 5‐fluorouracil and mitomycin C were planned for all patients. Oncological outcomes, acute and late toxicity profiles and pattern of failure were reported. Results: The 3‐year colostomy‐free survival rate was 64% (95% CI 0.52–0.75). The 3‐year local control, disease‐free and overall survival rates were 69% (95% CI 0.57–0.79), 71% (95% CI 0.59–0.80) and 79% (95% CI 0.66–0.87), respectively. The cumulative incidence of colostomies was 15.1% (95% CI 8.15–23.88) at 24 months. The cumulative incidence of cancer‐specific deaths was 16.4% (95% CI 8.60–26.47) at 36 months. Major acute toxicity consisted of hematological (G3–G4: 26%) and cutaneous (G3–G4: 16%) events. Only one case of ≥G3 late toxicity was documented. Conclusions: Simultaneous integrated boost IMRT and concurrent chemotherapy as per RTOG 0529 protocol seems to be safe and feasible with consistent oncological outcomes and a mild acute and late toxicity profile in anal cancer patients.